Development of Integrated Basic Physics Learning E-modules for Natural Disaster Mitigation to Improve Quality Learning - Finta Amalinda; Eka Dewi; Daud K Walanda; Darsikin Darsikin; I Komang werdhiana (Postgraduate, University of Mataram, 2025)
In an era of increasingly frequent natural disasters, integrating disaster mitigation into educational frameworks is crucial. This study addresses the need for innovative teaching materials that not only enhance basic physics understanding but also prepare students for challenges in disaster-prone regions. The research aims to develop a basic physics e-module integrated with disaster mitigation. The goal is to improve students' knowledge of physics and disaster preparedness, particularly in areas like Central Sulawesi. Using a Research and Development (R&D) approach with the ADDIE model, the study's findings show expert validators gave an average score above 4.00, lecturers rated the course 4.67, and there was an improvement in learning outcomes, with CI values ranging from 6.74 to 8.39 and an effect size (Cohen's d) of 4.17. The research concludes that e-modules can effectively enhance learning quality and disaster preparedness.